2015
DOI: 10.1111/1462-2920.12794
|View full text |Cite
|
Sign up to set email alerts
|

SecReT6: a web‐based resource for type VI secretion systems found in bacteria

Abstract: SecReT6 (http://db-mml.sjtu.edu.cn/SecReT6/) is an integrated database providing comprehensive information on type VI secretion systems (T6SSs) in bacteria. T6SSs are a class of sophisticated cell contact-dependent apparatuses involved in mediating antagonistic or synergistic communications between bacteria and/or bacteria and eukaryotes. These apparatuses have recently been found to be widely distributed among Gram-negative bacterial species. SecReT6 offers a unique, readily explorable archive of known and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
197
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(197 citation statements)
references
References 42 publications
0
197
0
Order By: Relevance
“…In silico analysis also showed that EHEC had another two vgr genes, vgrG-2 (z0707) and vgrE (z2262) located in the other regions of genome. We then used our integrated database SecReT6 (http://db-mml.sjtu.edu.cn/SecReT6/) to compare the T6SS sequences [25], and found that the components and gene organization of the T6SS gene clusters were highly conserved in pathogenic E . coli strains compared with other bacteria including V .…”
Section: Resultsmentioning
confidence: 99%
“…In silico analysis also showed that EHEC had another two vgr genes, vgrG-2 (z0707) and vgrE (z2262) located in the other regions of genome. We then used our integrated database SecReT6 (http://db-mml.sjtu.edu.cn/SecReT6/) to compare the T6SS sequences [25], and found that the components and gene organization of the T6SS gene clusters were highly conserved in pathogenic E . coli strains compared with other bacteria including V .…”
Section: Resultsmentioning
confidence: 99%
“…MAEC ECC-1470 also carries two T6SS determinants located on GI1 (designated as the first ECC-1470 T6SS, T6SS/1) and on GI8 (ECC-1470 T6SS/2), respectively. E. coli ECC-1470 T6SS/1 is classified as subtype i1 [66] or the second E. coli T6SS-2 phylogenetic cluster [67] and T6SS/2 as subtype i2 [66] or the first E. coli T6SS-1 cluster [67]. Subtype i1 T6SSs generally participate in interbacterial competition, subtype i2 T6SSs target eukaryotic cells and play a role in the infection process of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned methods specifically for T6SS effector prediction, some online bioinformatics tools or databases provide a suggestion for potential effectors, such as an effector protein predictor, secretEPDB (An et al, 2016, 2017); a T6SS database; SecReT6 (Li et al, 2015); and T346hunter, which can annotate homologs of type III, IV and VI secretion systems automatically (Martínez-García et al, 2015). For researchers working on Burkholderia spp., DBSecSys is an online database for the Burkholderia mallei and Burkholderia pseudomallei secretion system (Memišević et al, 2014, 2016).…”
Section: Past and Current Methods For Identifying T6ss Effectorsmentioning
confidence: 99%